Leggi ecclesiastiche e pubblicazione digitale. Le nuove frontiere della promulgazione nel diritto canonico (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Chiesa cattolica e new media: dalla stampa alla tecnologia online - 2. L’istituto della promulgazione nel diritto canonico: dalla promulgatio legis di tradizione romanistica al Codex Juris Canonici del 1917 - 3. La promulgazione delle leggi nel vigente Codex Juris Canonici - 4. La pubblicazione online delle leggi canoniche e le iniziative delle Conferenze Episcopali - 5. Le nuove frontiere digitali della promulgazione tra potenzialità e zone grigie.Ecclesiastical laws and digital publication. The new frontiers of promulgation in Canon LawABSTRACT: Technological evolution has redefined spaces and methods of communication also within the Catholic Church. The speed of information exchange, the possibility of reaching a large number of recipients and the absence of costs represent the advanteges of online communication. In addition to encouraging the use of “instruments of social communication” (can. 822 § 1), the Magisterium creates a close connection between these instruments and the mission of proclaiming the Gospel to all peoples. The diffusion of Information and Communication Technology (ICT) involved also the publication of canon laws and it asks about the possibility of using the Internet as a way of promulgating the law. In fact, it can offer potential solutions to the problems raised by the application of can. 8 CIC. The restrictions imposed by the Covid 19 pandemic have further favored the spread of instruments of digital communication. In this perspective, online promulgation could constitute a solution to the limits of canonical legislative governance, allowing the diffusion of legal texts, the relative knowledge and obligation. An intervention by the universal legislator on the matter could offer guarantees about the authenticity of the published document, its unchangeability and the certainty of publication time.